2021
DOI: 10.3390/math9192487
|View full text |Cite
|
Sign up to set email alerts
|

Strong Differential Superordination Results Involving Extended Sălăgean and Ruscheweyh Operators

Abstract: The notion of strong differential subordination was introduced in 1994 and the theory related to it was developed in 2009. The dual notion of strong differential superordination was also introduced in 2009. In a paper published in 2012, the notion of strong differential subordination was given a new approach by defining new classes of analytic functions on U×U¯ having as coefficients holomorphic functions in U¯. Using those new classes, extended Sălăgean and Ruscheweyh operators were introduced and a new exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Numerous novel operators have been defined, their properties have been studied, and new families of exceptional univalent functions have been defined using these novel operators, leading to the discovery of remarkable results. A number of mathematicians have simultaneously produced exciting results in a range of research fields involving GFT using linear combinations of two operators, as demonstrated in several very recent papers [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous novel operators have been defined, their properties have been studied, and new families of exceptional univalent functions have been defined using these novel operators, leading to the discovery of remarkable results. A number of mathematicians have simultaneously produced exciting results in a range of research fields involving GFT using linear combinations of two operators, as demonstrated in several very recent papers [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%